Hierarchical Milankovitch and sub-Milankovitch cycles in the environmental magnetism of the lower Shahezi Formation, Lower Cretaceous, Songliao Basin, northeastern China - Zhang, Shujing; Wu, Huaichun; Zhang, Shihong; Yang, Tianshui; Li, Haiyan; Fang, Qiang; Shi, Meinan (Frontiers in Earth Science, 2023)
SK-2 borehole in Songliao Basin provides unprecedented geological materials for investigating the Early Cretaceous continental paleoenvironment and paleoclimate in northeastern China. The lacustrine successions of the lower Shahezi (K1sh) Formation at the depth from 4542 to 5695 m is systematically studied using environmental magnetism and cyclostratigraphy in this study. Magnetic analysis reveals an inverse correlation between magnetic susceptibility (MS) and lithological ranks in fine clastic sediments, with the highest values in mudstones and the lowest in sandstones. The main magnetism carriers in the lower K1sh are pseudo-single-domain (PSD) and/or multi-domain (MD) magnetite with minor presence of the hematite. MS was used to further explore the genesis of the environmental and climatic variations through cyclostratigraphic analysis. Sedimentary cycles of 113 m, 34 m, 13 m and 6 m can be identified in the power spectrum, which are interpreted as long and short eccentricity, obliquity, and precession cycles, demonstrating the impact of astronomical cyclicity on sedimentary rhythmicity. A floating astronomical time scales (FATS) of 4090 kyr and 4148 kyr were established by tuning the inferred long and short eccentricity cycles to the artificial 405-kyr and 105-kyr orbital eccentricity curves respectively. The estimated sediment accumulation rate around 28 cm/kyr confirms the rapid deposition process within the faulted lacustrine basin. Based on this study, the lake level oscillations in Songliao Basin are assumed to be shaped by long and short eccentricity, precession and semi-precession during Early Cretaceous. This study also indicates that the sand-mudstone alternations deposition in K1sh is most likely driven by the seasonal discrepancies of summer insolation during semi-precession periods.